OFR-123-77 Development And Performance Of A Field Calibration Light Source - Richard A. Walker (The National Institute for Occupational Safety and Health (NIOSH), 1976)
This report describes the development and performance of a multi-level, multi-function Calibration Light Source designed for field-calibration of a group of specific photometers. The Calibration Source is capable of providing ±35% accuracy calibrations at all of the following levels: 0. 05 foot-Lamberts, 6 foot-Lamberts, 6 foot-candles and 20 foot-candles. The Source was found to provide constant light output to within 1% over 50 hours of lamp operation and for line voltage variations of ±25%. It is compact and light-weight (11 pounds), and can be easily transported and used by one man in normal office environments (without requiring a darkroom).